Mega-Mining, Contract Archaeology, and Local Responses to the Global Order in Argentina - Jofre, Ivana Carina (2015)
This paper shows that contract archaeology activities geared to large mining projects in Argentina articulates with a global discourse on heritage that seeks to patrimonialize places of Indigenous memory. However, these hegemonic moves for the creation of a sense of the “real”—which positions mining as an unavoidable and even desired “reality” and mining corporations as sensitive and responsible actors—are confronted by counter-hegemonic forces, among which current narratives of aboriginality are prominent.